Controlled dynamic remodeling of the spliceosome active site enables the first step of splicing - Gianfranco Martino; Jacopo Manigrasso; Giuseppina La Sala; Marco Marcia; Marco De Vivo (Proceedings of the National Academy of Sciences, 2026)
Recent cryoelectron microscopy data have revealed significant conformational rearrangements of the megadalton spliceosome structure during splicing, an essential catalytic process for maturing most human transcripts. However, the molecular trigger of these structural rearrangements for splicing catalysis remains unclear at the atomic level. Here, by analyzing a consistent dataset of multicomponent spliceosome structures, we identified a minimal set of positively charged residues whose dynamic action remodels the spliceosome active site during the first step of splicing. Through equilibrium and enhanced sampling molecular dynamics simulations of multiple splicing intermediates (>2M atoms), we uncover how these residues dynamically operate in coordination with the transient, temporally ordered binding of key spliceosomal proteins (Prp11, Prp8, and Yju2) at the spliceosome core. Our findings reveal a molecular mechanism that ensures precise and timely spliceosome activation, opening promising directions to probe splicing regulation and potentially target its dysfunction in diseases, with broad implications for drug discovery and medicine.